Comparisons of Different Preparation Methods in Computed Tomography Urography - Bozdag, Pinar Gundogan; Serhatlıoglu, Selamı; Kocakoc, Ercan; Poyraz, Ahmet Kursad (My University, 2020)
Objective: Computed Tomography Urography (CTU) is an imaging method used to assess thekidneys, ureters, and bladder in the excretory phase by computed tomography (CT) withintravenous contrast media (IVCM). Our aim is to compare the five different methods performed forpatient preparation prior to CTU, and to demonstrate their superiorities and disadvantagescompared to each other.Materials and Methods: A total of 100 patients who underwent CTU scans with an indication as aresult of their examinations were included in our study. These cases were randomly divided into 5groups of 20. Water was applied to the first group. Saline was administered to the second group. Inthe third group, 0.1 mg/kg furosemide was administered intravenously following a 250 mL saline.Intravenous furosemide was administered to the fourth group. Intravenous furosemide wasadministered to the fifth group after they received water. Ureters were compared with each otheraccording to the degree of opacification in proximal, medial, and distal segments in standard CTU.Results: By comparing the groups in pairs; there was a significant difference between Group II andthe other four groups for the proximal ureter segment, and between Group II and Group III and IVfor the medial and distal ureter segments (P<0.05). Conclusion: We believe that intravenous saline didn’t increase ureter opacification compared tothe other groups due to different patient populations and hydration conditions, instead salineincreased ureter contractions and homogeneous diuresis related to furosemide.
Keywords: Genel ve Dahili Tıp; Üroloji ve Nefroloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme